Buovo d’Antona fra originale veneziano e suo adattamento yiddish: la narrazione cavalleresca veicolo delle ideologie - Artico, Davide (Romanica Silesiana, 2020)
The paper contains some partial findings of a comparative research on the chivalry romance Buovo d’Antona as printed in Bologna and in Venice in the 1480s in a number of different, yet quite similar one to another, incunables; and its ottava rima adaptation in yiddish-taytsh, made by Elye Bokher (Elia Levita) in Padua around 1507, and then published as Bovo-Buch in Isny, Württemberg, as late as 1541. Respectively, the narratives implicitly deliver two different ideologies, meant as consequent sets of socially shared convictions about the good living. In particular, the place of women in society and the family, or better said, the male representation thereof, substantially differs in the Yiddish adaptation compared to the Venetian original.